µTodo tosco y sin labrar»: el model conventual de santa Teresa i el seu reflex en la normativa arquitectònica de l'orde carmelità descalç. - NARVÁEZ, CARME (Scripta)
The concept of life in enclosed monastery set out by Saint Teresa determined the nature of the buildings tackled in the breast of the congregation of Discalced Carmelites. The simplicity and the narrowness required by the founder in the establishment of the new convents, turned into precepts of forced fulfillment by part of the authorities of the religious order, and they remained collected in the diverse internal constitutions generated along the 17th and 18th centuries. This article analyses the constructive models established since the beginning of the congregation and the way in which they were applied subsequently.